Microwave measurement and imaging for multiple corrosion cracks in planar metals. (November 2020) - Yu, Yating; Li, Yanbin; Qin, Hong; Cheng, Ximeng
Abstract: Metal structures (such as buried pipelines, steel bridges) are subjected to long-term corrosion in the harsh environment, once the anticorrosion layer coated on the metals peeled off, corrosion cracks will occur and result in pipeline leaks, bridge fractures and other fatal effects that endanger human life and property safety. Therefore, an approach to characterize the location, size and boundary of the corrosion cracks is essential to guarantee the structures' health. In this paper, a microwave measurement and imaging approach is proposed to characterize the multiple corrosion cracks in planar metal. Firstly, a numerical model based on finite integral technique (FIT) and an experimental platform is established, respectively. Secondly, for the typical corrosion cracks, the relationships between the location as well as the size of the cracks, and the phase of the reflection coefficient are investigated. Then, an approach to characterization the location and size of the corrosion cracks is proposed. Finally, the boundary of the corrosion cracks is imaged by an improved canny algorithm. The microwave measurement and imaging approach proposed can quantitatively characterize the number, location, size and boundary of the cracks, while the cracks can be visually recognized by imaging Graphical abstract: Unlabelled Image Highlights: Microwave measurement and imaging for multiple corrosion cracks is proposed. The penetrating corrosion cracks and pitting corrosion cracks is studied. The location and size of penetrating crack is determined by the phase curve. The location and size of pitting crack is denoted by the phase gradient curve. The boundary of the corrosion cracks is visualized by the microwave imaging.